The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1002/1521-4095(20020318)14:6<461::aid-adma461>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Peptides Bound to Silicone Membranes and 3D Microfabrication for Cardiac Cell Culture

Abstract: Mechanical load and stress are exerted upon heart muscle tissue in vivo, leading to changes in cellular biochemistry and physiology. Understanding the fundamental mechanisms of mechanical transduction at the cellular level requires the development of physiologically relevant models of cells in vitro. Silicone elastomers are widely used as flexible cell culture substrates for in‐vitro cardiac mechano‐biological studies. We describe here the use of peptide binding to and microfabrication of silicone elastomer me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…A long-term goal of our group is to use biotechnological approaches to recapitulate both the architecture and surface chemistry (1,20), in vitro, to obtain a more biological phenotype in culture. In other studies, cells have been embedded into extracellular matrix proteins in an attempt to recapitulate some of their native environment.…”
supporting
confidence: 60%
“…A long-term goal of our group is to use biotechnological approaches to recapitulate both the architecture and surface chemistry (1,20), in vitro, to obtain a more biological phenotype in culture. In other studies, cells have been embedded into extracellular matrix proteins in an attempt to recapitulate some of their native environment.…”
supporting
confidence: 60%
“…Control over murine connective tissue cell adhesion has been achieved by selective functionalization of ridges and grooves on microfabricated polymer surfaces with fibronectin (cell adhesive) and hydrophobic organosilanes (cell repulsive) [139]. Photolithographically patterned silicone elastomers have also been used to culture cardiac myocytes in vitro [140]. Five-to 10-m-wide grooves on the surface of the silicone allow directional growth of the cells, while functionalization of the silicone surface with an RGD (Arg-Gly-Asp) peptide sequence enhanced the adhesion of the myocytes to the surface.…”
Section: Mems Technology For Tissue Engineeringmentioning
confidence: 99%
“…Clark et al reported that cell-cell contact was a major determinant in the development of spontaneous activity (beating) in adult feline cardiomyocyte cultures [14]. The culture surface had a significant role, not only in the attachment [15] of the cells, but also in cell signaling. Simpson et al showed that the phenotype of cardiac myocytes was determined by the culture substrate (type I collagen) through a signaling process which involved the cardiac α-1 or β-1 integrin chain [16].…”
Section: Introductionmentioning
confidence: 99%